Burnout, Job Demands, and Work Stress Among Nurses: The Moderating Role of Workplace Compassion - Rindy Pransiska; Dedi Muhammad Siddiq; Catur Setiya Sulistiyana; Nhan Cam Tri; Prattana Srisuk (Indonesian Journal Economic Review (IJER), 2026)
This study aims to examine the effects of burnout and job demands on work stress, with workplace compassion as a moderating variable among nurses at a Regional General Hospital in Indonesia. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 153 nurses through a structured questionnaire employing a Likert Scale. The findings indicate that both burnout and job demands have a positive and significant effect on work stress. Furthermore, workplace compassion functions as a significant moderating variable with nuanced effects. Specifically, workplace compassion acts as a buffering mechanism in the relationship between job demands and work stress, reducing the negative impact of high job demands. However, it simultaneously strengthens the relationship between burnout and work stress, suggesting a complex interaction between emotional exhaustion and compassionate workplace dynamics. These findings support the job demands – resources (JD-R) theory and highlight the importance of hospital management to foster a compassionate organizational culture to mitigate work stress and enhance nurses’ well-being.